Neuroprotective potential for mitigating ischemia-reperfusion-induced damage - Zi Ye; Runqing Liu; Hangxing Wang; Aizhen Zuo; Cen Jin; Nan Wang; Huiqi Sun; Luqian Feng; Hua Yang (Neural Regeneration Research)
Reperfusion following cerebral ischemia causes both structural and functional damage to brain tissue and could aggravate a patient’s condition; this phenomenon is known as cerebral ischemia-reperfusion injury. Current studies have elucidated the neuroprotective role of the sirtuin protein family (Sirtuins) in modulating cerebral ischemia-reperfusion injury. However, the potential of utilizing it as a novel intervention target to influence the prognosis of cerebral ischemia-reperfusion injury requires additional exploration. In this review, the origin and research progress of Sirtuins are summarized, suggesting the involvement of Sirtuins in diverse mechanisms that affect cerebral ischemia-reperfusion injury, including inflammation, oxidative stress, blood–brain barrier damage, apoptosis, pyroptosis, and autophagy. The therapeutic avenues related to Sirtuins that may improve the prognosis of cerebral ischemia-reperfusion injury were also investigated by modulating Sirtuins expression and affecting representative pathways, such as nuclear factor-kappa B signaling, oxidative stress mediated by adenosine monophosphate-activated protein kinase, and the forkhead box O. This review also summarizes the potential of endogenous substances, such as RNA and hormones, drugs, dietary supplements, and emerging therapies that regulate Sirtuins expression. This review also reveals that regulating Sirtuins mitigates cerebral ischemia-reperfusion injury when combined with other risk factors. While Sirtuins show promise as a potential target for the treatment of cerebral ischemia-reperfusion injury, most recent studies are based on rodent models with circadian rhythms that are distinct from those of humans, potentially influencing the efficacy of Sirtuins-targeting drug therapies. Overall, this review provides new insights into the role of Sirtuins in the pathology and treatment of cerebral ischemia-reperfusion injury.